Come rain or come shine [compact disc, unabridged] - Karon, Jan, 1937- (Karon, Jan, 1937- Mitford years., 2015)
Over the course of ten Mitford novels, fans have kept a special place in their hearts for Dooley Kavanagh, first seen in At Home in Mitford as a barefoot, freckle-faced boy in filthy overalls. Now, Father Tim Kavanagh's adopted son has graduated from vet school and opened his own animal clinic. Since money will be tight for a while, maybe he and Lace Harper, his once and future soul mate, should keep their wedding simple. So the plan is to eliminate the cost of catering and do potluck. Ought to be fun.